2002
DOI: 10.1002/1521-3951(200212)234:3<887::aid-pssb887>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characterization of AlxGa1?xN Alloys (x < 0.7) Grown on Sapphire or Silicon

Abstract: The optical properties of Al x Ga 1--x N samples (x < 0.7) have been studied by photoluminescence (PL) and reflectivity in the 10-300 K temperature range. Various physical properties have been studied as a function of composition, such as Stokes shift, alloy broadening, exciton localization, and Huang-Rhys factor. Up to x % 0.3, a band gap bowing factor of $0.9 eV accounts for the variation of PL and reflectivity energies. At higher compositions, luminescence energies deepen with regard to this behaviour. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 16 publications
4
24
0
1
Order By: Relevance
“…Similar behavior has been reported previously for the In x Ga 1Ϫx N 29 and Al x Ga 1Ϫx N epilayers. 11,13,24,25 In the In x Ga 1Ϫx N-based light-emitting device structures, In alloy inhomogeneity, and/or quantum-dot-like In phase separation have been proposed as the origin of localized states, and temperature-induced blueshift attributed to band-tail states in the density of states has been observed. The theoretical calculation also predicts a high tendency of phase separation in the In-Ga-N alloy system, but not in Al x Ga 1Ϫx N epilayers.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…Similar behavior has been reported previously for the In x Ga 1Ϫx N 29 and Al x Ga 1Ϫx N epilayers. 11,13,24,25 In the In x Ga 1Ϫx N-based light-emitting device structures, In alloy inhomogeneity, and/or quantum-dot-like In phase separation have been proposed as the origin of localized states, and temperature-induced blueshift attributed to band-tail states in the density of states has been observed. The theoretical calculation also predicts a high tendency of phase separation in the In-Ga-N alloy system, but not in Al x Ga 1Ϫx N epilayers.…”
Section: Methodssupporting
confidence: 90%
“…However, Cho et al 23 showed that the Stokes shift between the PL emission peak energy and PLE absorption edge monotonically increases with varying Al contents. Comparing our results with previously reported one, [11][12][13][14][15][16][23][24][25][26][27] the large Stokes shift between PL emission and OA or PC strongly implies that the potential fluctuation does exist in Al x Ga 1Ϫx N epilayers. These results can be understood in terms of increase in the depth of localized states from the band edge of Al x Ga 1Ϫx N epilayers with large Al contents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…at high x to transitions involving mainly the G 9 or the G 7C valence bands and only weakly the absolute G 7B valence band maximum. This explains, at least partly, the Stokes shift increase [14]. It seems that the reflectivity data are still keeping a bowing parameter of 1 eV, but the increasing uncertainty on the A exciton energy value taken from reflectivity measurements makes it difficult to conclude on the exact value of the bowing parameter for xO0.4.…”
Section: Resultsmentioning
confidence: 99%
“…Two longitudinal optical (LO) phonon replicas of the I 2 peak, separated by an energy of 93 meV, are also observed. The fullwidth at half-maximum (FWHM) of the PL peak of the undoped layer is 32 meV, in good agreement with literature [19]. This is attributed to alloy inhomogeneous broadening.…”
Section: Hall Effect Measurementsmentioning
confidence: 99%